2015
DOI: 10.1177/147470491501300101
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Marital Conflict in Five Cultures

Abstract: This analysis of previously collected data examined four fitness-relevant issues for their possible role in marital conflict. These were sex, finances, division of labor, and raising children, selected in light of their pertinence to sex differences in reproductive strategies. Over 2,000 couples in five diverse cultures were studied. Marital conflict was assessed by the Problems with Partner scale, which was previously shown to demonstrate measurement invariance across cultures and genders. All four issues wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 57 publications
3
10
0
4
Order By: Relevance
“…Importantly, however, the way people seek and provide support differs by culture, and these differences are consistent with the cross‐cultural studies reviewed above about the expression of love and approach to conflict (Dillion et al, 2015; MacNeil & Adamsons, 2014; Ting‐Toomey, 1991; Wilkins & Gareis, 2006). Thus, the CBR 2 model suggests that similarity between partners on emotional processes and relationship norms may promote more effective responsiveness to a partner's emotional disclosures, which in turn may help to build trust, increase communication and mutual respect between intercultural partners.…”
Section: The Cbr2 Modelsupporting
confidence: 78%
See 1 more Smart Citation
“…Importantly, however, the way people seek and provide support differs by culture, and these differences are consistent with the cross‐cultural studies reviewed above about the expression of love and approach to conflict (Dillion et al, 2015; MacNeil & Adamsons, 2014; Ting‐Toomey, 1991; Wilkins & Gareis, 2006). Thus, the CBR 2 model suggests that similarity between partners on emotional processes and relationship norms may promote more effective responsiveness to a partner's emotional disclosures, which in turn may help to build trust, increase communication and mutual respect between intercultural partners.…”
Section: The Cbr2 Modelsupporting
confidence: 78%
“…Studies have also found cultural differences in conflict styles between Western and East‐Asian participants. For instance, participants with more collectivist values prefer avoidant approach styles during conflict, while those with more independent values prefer more direct approaches (Dillion et al, 2015; MacNeil & Adamsons, 2014; Ting‐Toomey, 1991). Other studies have found that African Americans report higher levels of demand behaviors than Asian Americans, and European Americans have been found to prefer more accommodating styles (e.g., cooperative but assertive) compared to Puerto Ricans (Cionea, Leeson, Bruscella, & Van Gilder, 2015; Corey, Fok, & Payne, 2014).…”
Section: The Cbr2 Modelmentioning
confidence: 99%
“…O MARQ tem sido utilizado em várias pesquisas envolvendo diferentes culturas para analisar aspectos dos relacionamentos afetivos, entre os quais se podem destacar: diferenças e similaridades sexuais entre os cônjuges , o impacto de filhos na satisfação do relacionamento (Wendorf, Lucas, Imamoglu, Weisfeld, & Weisfeld, 2011), o efeito cultural e adaptativo da satisfação no relacionamento (Lucas et al, 2008), para predizer violência marital (Russel & Wells, 2000) e felicidade (Russel & Wells, 1994), bem como para comparar nível de conflito marital entre culturas (Dillon et al, 2015).…”
Section: Mensuração Do Amorunclassified
“…Todas las parejas estables con descendencia, con independencia de que exista vínculo matrimonial o no, experimentan, a lo largo de su relación, diferentes conflictos (Dillon et al, 2015); así, los niños a menudo se encuentran expuestos a ellos, pudiendo perjudicar su crianza, al comportamiento parental y a la relación con sus progenitores (Shamir, Schudlich, y Cummings, 2001). De esta manera, se considera el conflicto interparental como un importante factor adverso para los hijos (Cummings y Davies, 2010).…”
unclassified
“…De esta manera, se considera el conflicto interparental como un importante factor adverso para los hijos (Cummings y Davies, 2010). Sin embargo, cuando las parejas comparten amabilidad, confianza y comprensión, los conflictos entre ellos se resuelven (Dillon et al, 2015) y pueden gestionarlos de forma positiva, amigable y constructiva lo que, a su vez, incide en la crianza de los hijos, llegando a aumentar su sentimiento de seguridad y bienestar en la familia (Zemp, Bodenmann, y Cummings, 2016). En este sentido, los conflictos pueden promover el crecimiento personal, incluso en familias separadas (Treloar, 2019).…”
unclassified